Metadiscourses of resistance. Harangues, proclamations and committed poetry in the Catalan press during the Spanish Civil War (1936-1939) - Luengo López, Jordi; García Fuentes, Raquel (Historia y Comunicación Social, 2022)
Beyond the discourses that can be found in the Catalan press during the Spanish Civil War, reflected both in their anti-fascism against the advance of the Nationalist army and in their perseverance in Republican ideals, an amalgam of messages provided evidence of such resistance. We have found a number of arousing harangues and some passages from “committed poetry”, which exuded a dormant spirit of irreverence towards a regime that was denying freedom to an entire nation. Through the singularity of Catalonia, one of the latest territories to be defeated, we will analyze how, thanks to language, these metadiscourses instilled a feeling of resistance in the collective imaginary against the military “conquest”.